Burden and correlates of readmissions related to pulmonary edema in US hemodialysis patients: a cohort study. Issue 7 (25th December 2017) - Plantinga, Laura C; King, Laura M; Masud, Tahsin; Shafi, Tariq; Burkart, John M; Lea, Janice P; Jaar, Bernard G
ABSTRACT: Background: Pulmonary edema is prevalent and may be a common cause of hospital readmissions in hemodialysis patients. We aimed to estimate the national burden of, and identify correlates of, readmissions related to pulmonary edema among hemodialysis patients. Methods: In this retrospective cohort study using national registry data, we identified prevalent US hemodialysis patients ( n = 215 251) with index admissions while under Medicare primary coverage in 2011–13. We defined readmissions as admissions occurring within 30 days of the index discharge and pulmonary edema-related readmissions as readmissions with discharge diagnoses of fluid overload, heart failure or pulmonary edema. Multivariable logistic regression models were used to determine odds ratios (ORs) for pulmonary edema-related readmissions by patient and index admission characteristics. Results: About one-quarter (23%) of index hospital admissions were followed by a readmission, with nearly half (44%) of the readmissions being associated with pulmonary edema. The strongest independent correlate of pulmonary edema-related readmission was a pulmonary edema-related index admission [OR = 2.32; 95% confidence interval (CI) 2.22–2.41]. With the exception of dialysis vintage <1 year (OR = 1.18; 95% CI 1.14–1.22), chronic obstructive pulmonary disease (OR = 1.34; 95% CI 1.29–1.38), dialysis non-compliance (OR = 1.53; 95% CI 1.41–1.64) and congestive heart failure (OR = 1.85; 95% CI 1.77–1.93), patient characteristics were not generally associated with higher risk of pulmonary edema-related readmission. Conclusions: Readmissions related to pulmonary edema are common in hemodialysis patients. Interventions aimed at preventing such readmissions could have a substantial impact on readmissions overall, particularly targeted at incident hemodialysis patients with a prior history of heart failure and patients initially admitted for pulmonary edema.